Surface modification of all-inorganic halide perovskite nanorods by a microscale hydrophobic zeolite for stable and sensitive laser humidity sensing. Issue 25 (27th May 2020) - Li, Ruxue; Yu, Jiahao; Wang, Sheng; Shi, Yueqing; Wang, Zhaojin; Wang, Kai; Ni, Zhenhua; Yang, Xuyong; Wei, Zhipeng; Chen, Rui
Abstract : CsPbBr3 nanorods modified by hydrophobic zeolite exhibits high stability and enhanced scattering that allowing for high quality random lasing. Using lasing rather than photoluminescence as humidity sensing signal makes the sensing more reliable. Abstract : Perovskite materials are very sensitive to the environment which is beneficial for humidity sensing. However, the existing illuminating humidity sensor has low luminous efficiency and sensitivity. Besides, the stability of perovskite materials remains a key issue to be resolved. Compared to luminescence, lasing is much more sensitive to the surrounding environmental situation. However, humidity sensing based on perovskite lasing has not been reported so far. In this work, all-inorganic halide perovskite CsPbBr3 nanorods with an optical gain coefficient as high as 954 cm −1 were designed and fabricated. Moreover, a microscale hydrophobic zeolite was introduced to modify perovskites for improved stability. It is interesting to note that the hydrophobic zeolite introduces strong scattering which is beneficial for three-dimensional random lasing with a quality ( Q ) factor of 2263. Through the strategy of using lasing instead of luminescence, optical stability and sensitive laser humidity sensing were demonstrated, and it exhibits high sensitivity and good reliability. This work provides a new idea of improved stability of perovskites, which will promote the practical application of perovskite materials and devices.